ON THE DIOPHANTINE EQUATION 9^x+9^y+n^z=w^2 - ศิระวรกุล, อภิรัฐ; ตาดี, สุธน (วารสารวิทยาศาสตร์และเทคโนโลยี มหาวิทยาลัยธนบุรี, 2024)
In this work, we give some conditions for the non-existence of solutions of the Diophantine equation , where is a positive integer and are non-negative integers. Moreover, we find all solutions of this equation for some positive integer .